«We Should Never Write Without Feeling». Studi su William T. Vollmann. Introduzione (ENTHYMEMA, 2022)
Presentazione della sezione “«We Should Never Write Without Feeling». Studi su William T. Vollmann”.Introduction to the monographic section “’We Should Never Write Without Feeling.’ Studies on William T. Vollmann”.